Factors that play a role in building resilience, autonomy, and sustainability of smallholder coconut farming in Aceh Province: Faktor-faktor yang berperan dalam membangun resiliensi, kemandirian, dan keberlanjutan usaha kelapa rakyat di Provinsi Aceh - Sulistyorini, Henny; Sumardjo, Sumardjo; Fatchiya, Anna; Purnaningsih, Ninuk; Cahyana, Destika (Analisis Kebijakan Pertanian, 2025)
Smallholder coconut plantation in Aceh Province faces increasing sustainability risks due to low farmer incomes driven by declining plantation areas, ageing trees, limited access to technology and extension services, and weak farmer institutions. Nevertheless, smallholder coconut plantations remain strategically important as a source of food, farmer income, industrial raw materials, employment opportunities, and environmental conservation. Therefore, strengthening farmers’ capacity and resilience is crucial to effectively managing coconut-based farming. This study examines the interrelationships among farmer group functions, farmer group leadership, social capital, farmer resilience, farmer autonomy, and the sustainability of smallholder coconut farming. The study was conducted in 2014 in the Regencies of Aceh Besar, Simeulue, and Bireuen, using a survey of 277 coconut farmers. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM). The study results show that the functions of farmer groups and the roles of their leaders had a positive and significant influence on autonomy, and social capital had a positive and significant influence on farmer resilience. Furthermore, farmer resilience was positively associated with farmer autonomy and coconut farming sustainability, and farmer group leadership also directly influenced farmer autonomy. To support the sustainability of smallholder coconut farming in Aceh, based on these findings, it is recommended that the government and regional governments strengthen social and institutional capacities through farmer groups, primarily through strengthening social networks and trust, enhancing the role of farmer group leaders as motivators and facilitators, and strengthening farmer groups as platforms for collective learning and cooperation.